Aplikasi Edukasi Pengenalan Profesi Pemadam Kebakaran Berbasis Augmented Reality - Andhik Ampuh Yunanto; Dina Ayu Fitriana; Muhammad Fajar Mukhti; Monica Kristania; Nadhif Nadhif (Jurnal Informatika Universitas Pamulang, 2020)
In this era, science and technology continue to develop significantly. One technology that is developing rapidly is information technology. This technological development can be used by the community and developers to help their work. One of the benefits of using this information technology is that it can help in the field of education. In addition, there are lots of cutting-edge technologies that are already sophisticated, namely Augmented Reality (AR) technology. In providing education to the younger generation, there are many insights that must be taught in addition to compulsory lessons in school. One of them is an insight into the use of internal fire extinguishers. Until now people tend to lack understanding of how this tool works because it is considered insignificant. Even though the fact is this is important to equip someone when one day there will be a fire. So that in this study proposes the development of an interactive learning application regarding fire extinguishers. This research has several stages including the identification of educational materials, the design and development of educational media, and testing of user convenience for early childhood where they are the target users of this application. This learning application built is a learning platform for children based on Augmented Reality. The test results show that this application gets positive feedback from child users where on average it gives a value of 9. So it can be concluded that child users can learn how the firefighting profession works and children can immediately practice it interactively through this learning application.